Chapter 2 - A self-assessment, and a tutorial in Excel - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED Am I aware of the basics of scientific writing required to write an informative report? Do I remember the basics of mathematics? How do I use statistics to plan and analyze my field or experimental data? How to lose the fear of using a spreadsheet? How to do basic repetitive calculations? How to present figures and reports in scientific style? How to efficiently select and summarize sub-groups of data?